Neurodevelopmental problems in pre-school children in rural Western Cape, South Africa: is community screening feasible? - Ben Truter; Christopher Gillberg; Amy L. Slogrove; Petra Conradie; Eva Billstedt; Lucy Thompson (BMC Psychiatry)
Abstract Background There is no standard public health screening for neurodevelopmental disorders in pre-school children in South Africa. There are pragmatic challenges in implementing such a programme in under-resourced regions. This study aimed to assess the feasibility of introducing a two-stage screening model for neurodevelopmental disorders among pre-school children in the rural Western Cape, South Africa. Methods We adopted a mixed methods approach to evaluate the feasibility of using a brief screening questionnaire, the ESSENCE-Q, translated into local languages (Afrikaans and isiXhosa), through verbal administration to mothers of pre-school children by trained research assistants without professional health qualifications within a cross-sectional ESSENCE-Q validation study. A focus group interview with research assistants who conducted the screening was analysed using reflexive thematic analysis. Feedback from participating mothers was obtained through a simple verbally administered questionnaire, rating 7 items on a Likert scale. Finally, the research team’s field notes were reviewed to critically assess feasibility. Results The focus group interview identified areas of logistical challenge but highlighted positive reception among mothers. Since mothers generally had low levels of education and literacy, time was required to clarify certain child development concepts during screening. The in-person mode of engagement and flexibility of processes, including the use of a visual consent booklet, supported feasibility. Considerable resource limitations and trauma were encountered. Training key community members to administer the ESSENCE-Q for future studies or screening projects was considered feasible, provided neurodevelopmental training and trauma support is provided. Feedback from mothers was consistently positive, although unavoidable delays between assessment and feedback may have impacted this data. Identified challenges can be adequately addressed through practical adaptations. Discussion Thorough preparation prior to commencing screening is considered essential for feasibility, including community-based stakeholder consultation, broad consultation around translated screening questionnaires, and preparation for diagnostic assessment. Ongoing support to mother–child recipients as well as those administering the screening, is required. The experience of participating mother–child pairs must be placed at the centre of community-based screening processes. Long term sustainability requires adequate training, supervision and psychological support for those administering such processes.